Sex hormone supplementation improves breathing and restores respiratory neuroplasticity following C2 hemisection in rats - Barok, Rebecca; Grittner, Jessica M. L.; Miller, Shawn; Dougherty, Brendan J. (Frontiers in Physiology, 2024)
In addition to loss of sensory and motor function below the level of the lesion, traumatic spinal cord injury (SCI) may reduce circulating steroid hormones that are necessary for maintaining normal physiological function for extended time periods. For men, who comprise nearly 80% of new SCI cases each year, testosterone is the most abundant circulating sex steroid. SCI often results in significantly reduced testosterone production and may result in chronic low testosterone levels. Testosterone plays a role in respiratory function and the expression of respiratory neuroplasticity. When testosterone levels are low, young adult male rats are unable to express phrenic long-term facilitation (pLTF), an inducible form of respiratory neuroplasticity invoked by acute, intermittent hypoxia (AIH). However, testosterone replacement can restore this respiratory neuroplasticity. Complicating the interpretation of this finding is that testosterone may exert its influence in three possible ways: 1) directly through androgen receptor (AR) activation, 2) through conversion to dihydrotestosterone (DHT) by way of the enzyme 5α-reductase, or 3) through conversion to 17β-estradiol (E2) by way of the enzyme aromatase. DHT signals via AR activation similar to testosterone, but with higher affinity, while E2 activates local estrogen receptors. Evidence to date supports the idea that exogenous testosterone supplementation exerts its influence through estrogen receptor signaling under conditions of low circulating testosterone. Here we explored both recovery of breathing function (measured with whole body barometric plethysmography) and the expression of AIH-induced pLTF in male rats following C2hemisection SCI. One week post injury, rats were supplemented with either E2 or DHT for 7 days. We hypothesized that E2 would enhance ventilation and reveal pLTF following AIH in SCI rats. To our surprise, though E2 did beneficially impact overall breathing recovery following C2-hemisection, both E2 supplementation and DHT restored the expression of AIH-induced pLTF 2 weeks post-SCI.